2018
DOI: 10.37358/rc.18.9.6570
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Chemical Profile of Some Melliferous Plant from Cluj Area, Romania, Using Different Extraction Techniques

Abstract: In this paper chemical compounds collected from melliferous plants (Cluj, Transylvania-area flora) using two methods and identified by GC-MS were presented. The melliferous plant studied : acacia, rape, linden and sun flower, represent a rich source of nectar and pollen used in the honey production. The methods were SPME (solid phase microextraction) coupled with GC-MS (gas chromatography and mass spectrometry) and alcoholic extraction of flowers followed by GC-MS. It was pursued in special the identifying of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to the studies of melisopalinological analysis made by authors from Romania, it was found that Apis mellifera honey bees from Romania collects pollen mainly from Brassica napus, Tilia, Heliantus and Robinia pseudocacia [13]. In other paper [14] we identified by SPME/GC-MS, the volatiles from melliferous plants: acacia, rape, linden and sun flower. This was the reason we have studied honey produced from these plants.…”
mentioning
confidence: 88%
“…According to the studies of melisopalinological analysis made by authors from Romania, it was found that Apis mellifera honey bees from Romania collects pollen mainly from Brassica napus, Tilia, Heliantus and Robinia pseudocacia [13]. In other paper [14] we identified by SPME/GC-MS, the volatiles from melliferous plants: acacia, rape, linden and sun flower. This was the reason we have studied honey produced from these plants.…”
mentioning
confidence: 88%